Electric field simulation of Ag nanoparticles induced by Femtosecond laser in welding process. (26th July 2020) - Ren, Xiaoying; Li, Xiao; Wei, Fengqi; Yin, Hailong; Wen, Yonghong
Abstract: The electric field distribution of Ag nanoparticles under femtosecond laser is simulated by solving Maxwell equations in this article. The results show that with the same laser energy, the coupling electric field between adjacent nanoparticles becomes stronger and stronger as the spacing between nanoparticles decreases, while the enhancement factor decreases rapidly when the spacing between nanoparticles is less than 1 nm, because under this condition, its mechanism includes not only the coupling of two dipoles, but also the electron tunneling between two surfaces. Besides laser energy, the electric field of Ag nanoparticles is greatly affected by the nanoparticles size and their spatial distribution. With the same laser energy and spacing, the smaller the particle size, the higher the peak value of electric field intensity, but the faster the attenuation with distance. In the polarization direction of the laser, the enhancement factor of the electric field is more obvious. When the laser acts on several Ag nanoparticles, the electric field of nanoparticles in the range of spot size is quite different from that of the nanoparticles outside the spot.